Estudio de impacto ambiental del área minera I.M.L-Santiago (código: 690487), ubicada en el barrio manzano de la parroquia Santiago del cantón Loja. - Sinchire Villalta, Maico Jeovanny (2014)
In this thesis project arises: do the " Study Environmental Impact of the mining area IML-SANTIAGO (code: 690487), located in the neighborhood Manzano of the parish Santiago of Canton Loja" in order to prevent and mitigate the impacts potential related the exploitation and closure of mine, based on the design and implementation of Environmental Management Plan aimed at sustainable development of the area. In developing of the baseline described medium such as found at the time of starting the project taking into account parameters of elements the physical, chemical, biotic, cultural and socio-economic, also proceeded to define the location in the draft of the actions and their areas of direct and indirect influence. Accordingly we proceeded to perform an environmental analysis allowed the identification and evaluation of environmental impacts likely to be generated by the project. This information was evaluated from a socio-economic and environmental terms, and with commitment by the mining company to comply strictly with the provisions of the Environmental Management Plan, the project is considered feasible. Once impact was evaluated proceeded to establish measures for prevention, correction, mitigation and compensation in the Environmental Management Plan which seeks to reduce the impacts level expected by the implementation of project, maintain environmental quality and ecological balance.